(untitled) (Research, Society and Development, 2025)
Fixed-Time Artificial Insemination (FTAI) is a reproductive biotechnology technique that has been widely used in cattle breeding, as it allows ovulation to be synchronized without the need to identify estrus. This makes group insemination easier and improves reproductive management. The objective of this research was to analyze the effectiveness of FTAI in Nelore cows aged between 2.5 and 6 years, which were subjected to a standardized hormonal protocol on a farm located in Cacoal/RO. The findings showed that FTAI significantly increases pregnancy rates, especially with the use of hormones such as progesterone, estradiol, prostaglandins and eCG, ensuring greater control over reproductive cycles. In addition to the benefits in reproduction, FTAI also favors the genetic progress of herds, reduces the interval between calvings and increases the uniformity of calves. However, its effectiveness depends on variables such as body condition, nutritional and health management practices, heat stress and the technical qualification of the team. In economic terms, this technique offers excellent cost-benefit, providing a significant financial return and potential for growth in productivity and environmental sustainability. In this way, IATF is positioned as a strategic tool for the modernization and intensification of livestock farming in Brazil.